Attitudes of Healthcare Professionals towards Digital Transformation: A Case Study of an Attica General Oncology Hospital - Chrysostomos Natsis; Sofoklis Chrysanthopoulos; Maria-Aggeliki Stamouli (Recent Updates in Disease and Health Research Vol. 9, 2024)
Purpose: The present study highlights the attitude of Health Professionals of the General Oncology Hospital of Attica towards integrated Hospital Information Systems (HISs) and the socio-demographic factors that shape them. Background: Health professionals and patients are becoming more educated and, at the same time, more demanding in terms of the use of information and communication technologies (ICT). The need for automation to be integrated into the health sector is highlighted by the growing requirement to handle the increasing volume of health information that is becoming more and more abundant, as well as the need to improve the productivity and efficiency of health professionals. Materials-Methods: A quantitative stratified sampling survey was conducted using the occupational category of the employees as a stratification variable. Data were collected using the standard Nurses Attitudes Towards Computerization (NATC) self-report questionnaire and Statistical analysis was conducted using SPSS-v25. Results: The employees of the General Oncology Hospital under study have a positive attitude toward the use of Hospital Information Systems (Mean=3.73, SD=0.54). Statistically significant differences between occupational categories were found only for the dimension of “Providing quality care to the patient” (p=0.007) and more specifically between nurses and doctors. Regarding the effect of demographic factors on the five dimensions that form the attitude of health professionals towards the HIS, only “gender” (p = 0.009) and “occupation categories” (p=0.007) seem to influence this attitude and specifically the dimension “Providing quality care to the patient”, whereas “previous experience in the use of computers at work” affects the dimension “Reduction in jobs” (p=0.009). The effect of gender was statistically significant only in terms of the “quality of care provided to patients” through the use of HIS. The analysis revealed that men hold a more positive attitude towards the use of computers compared to women. Conclusions: Employees at the General Oncology Hospital under study have a positive attitude toward the use of Hospital Informatics Systems (HISs), according to the statistical analysis of the data. Employees who now use personal computers for work tend to disagree with the idea that HIS will result in job losses, and men tend to have the most positive attitudes.